Soil respiration in shrub willow (Salix x dasyclados) biomass crop increased on the third year after removal - Aydin, Mirac; Pacaldo, Renato S.; Volk, Timothy A. (Inderscience Publishers, 2018)
The SWBC production system is not only a source of renewable energy, but also a carbon sink. However, one of the uncertainties in the greenhouse gas potential analysis of this system is soil CO2 efflux (F-c) rates after its termination. We examined the F-c rates for three years and determined the total CO2 production of SWBC fields following the termination and removal of SWBC fields. Four current SWBC fields of 5-, 12-, 14-, and 19-years old were used as sampling plots. The mean F-c rates did not differ statistically between ages (p = 0.66), and there was no significant interaction effect between age and year (p = 0.94) However, F-c rates significantly increased in the third year (p = 0.01). Annual cumulative F-c ratios at different seasons were 52% for summer, 26% for fall, 16% for spring, and 6% for winter.
Keywords: 13. Climate action; 15. Life on land